Manejo de solo de várzea para cultivo de soja, milho e forrageiras hibernais na fronteira oeste gaúcha - Goulart, Rafael Ziani (2016)
This study sought to understand the capacity of different management systems of the wetland soil for the maintenance of a physical environment capable of reducing the effect of hypoxia during the cycle dryland crops, as well as the relationship between soil management systems And the agronomic performance of the rainfed crops used in rotation with the irrigated rice. To meet the objective, dryland crops were cultivated in wetland area in the agricultural years of 2014/2015 (YEAR I) and 2015/2016 (YEAR II). In YEAR I, the soybean crop was planted in 3 management systems (conventional, chiseling and ridge). In YEAR II, four cultivars of soybean and a variety of maize were cultivated in 4 management systems (conventional, chiseling, ridge and chiseling + ridge). The four soybean cultivars consisted of different maturation groups (hyper-precocious to semi-late). This year, after the cultivation of soybeans, winter forages were cultivated (black oats, ryegrass and consortium ryegrass with black oats). The experimental design was in randomized blocks with 4 replicates. In YEAR II the experiment with soybean had the plots subdivided with the different maturation groups and afterwards with the different forage arrangements. In order to evaluate the hydro-physical properties modification caused by the different proposed treatments, soil density, total porosity, macroporosity, microporosity, saturated soil hydraulic conductivity, soil water infiltration rate, random roughness and the mean slope of the ridge in two years at three different times (at seeding, at 45 and 140 days after seeding: 0 DAS, 45 DAS and 140 DAS, respectively). In addition, a penetration resistance test was carried at 45 DAS in the YEARS I and II. Plant performance was measured by leaf chlorophyll content, established plants and grain yield for corn and soybean crops. The leaf area index in the soybean crop had also been measured. For the evaluation of the performance of the winter forages was measured the dry matter production of the aerial part. Chiseling alone or accompanied by the construction of the ridge provided a physical environment with greater drainage (infiltration rate), greater pore space occupied by air (macroporosity) and less resistance to penetration than conventional management systems and only with ridge. However, these effects are less intense over time and concentrate at depths smaller than the working depth of the scarifier stem. The shape obtained with the construction of the ridge suffered accommodation of approximately 41% in the crest / furrow slope during the summer period. The chiseling increased the productivity of soybeans, maize and forages in wetland soils, whether this is an isolated practice or associated to the construction of ridges. Ridges isolates construction had a contrasting effect on the soybean production in the two agricultural years, because it did not differ from the conventional system or because it resembled the chiseling and chiseling with ridge. There was no conclusive relationship between soybean cycle and its relation with grain yield. The results show that the chiseling helps to improve the hydro-physical properties responsible for reducing stress due to oxygen deficiency in wetland soils. However, the excess rainfall reduces the benefits provided by this management.